VELA AND MALA PALAGRUŽA - DIOMEDIAE INSULAE - Mithad Kozličić (Geodetski Glasnik, 2018)
Sailing route leading from central Dalmatia to the Gargano region was one of the most heavily travelled seaways in antiquity. On the one hand it is marked by the toponyms associated with Diomedes and his cult in historical and geographical sources (Diomedes' cape, Diomedes' city/cities, Diomedes' islands and Diomedes' sanctuary), and on the other hand by the information on the distance between the two coasts or some central Dalmatian islands and Italian coast of the Adriatic. Exceptional frequency of such sailing was supported by the fact that one could sail directly to the south or vice versa directly to the north which was of crucial importance in ancient navigation in theoretical and practical terms. Palagruža (Vela and Mala), the Islands of Diomedes in antiquity, were orientation landmarks of exceptional importance on this sea route. The text offers a detailed analysis of the most important historical and geographical information provided by the ancient writers who shed more light on such position of both islands of Palagruža in antiquity.